Total Quality Management Dimension and SME Performance: A Quantitative Approach (Global Business Management Review (GBMR), 2022)
The objective of this study is to measure the relationship between some TQM dimensions and business performance of SMEs. The study seeks to advance the understanding of TQM and also resolves some controversies that appear in the literature concerning the relationship between TQM dimensions and performance relationship. Using questionnaire, the data for this study was drawn from 367 SMEs operating in Punjab, Pakistan. Structural equation modeling (SEM) technique was used for analysis. The findings indicate that management leadership has a significant effect on business performance of SMEs, whereas, the customer focus and continuous improvement to business performance relationship were found not significant.